Bone scan in painful knee arthroplasty: obsolete or actual examination? - Niccoli, Giuseppe; Mercurio, Domenico; Cortese, Fabrizio (Acta Biomedica Atenei Parmensis, 2017)
ptic loosening, instability and infection are the major causes of TKA failure. For many years, nuclear medicine (NM) imaging was helpful to frame a painful total joint arthroplasty. The differentiation of septic from aseptic prosthetic loosening is critical. The latest AAOS guidelines to detect periprosthetic joint infection (PJI) restrict the role of NM scintigraphy. On the other hand, several studies suggest that NM imaging plays an important role in the evaluation of patients with painful prosthesis, but its specificity in differentiating aseptic loosening from infection is low. Moreover, scintigraphic exams showed different diagnostic accuracy in TKA compared to total hip arthroplasty (THA). Purpose: To assess and discuss current knowledges about the diagnostic value of the various scans in TKA failure alone. Methods: We perform a pubmed/medline search to identify all papers published in the literature matching the following key words: “total knee arthroplasty”, “bone”, “scintigraphy”, “imaging”, “three-phase”, “triple-phase”, “99mTc-HDP”, “99mTc-MDP”, “99mTc-hydroxymethane diphosphonate”, and “99m Tc-methylenediphosphonate”, “leukocyte scanning”, “labeled leukocyte scintigraphy”, “antigranulocyte”, “nuclear medicine”, “septic loosening”, “aseptic loosening” and “infection”. Results: Three phases bone scintigraphy results an early diagnostic screening test or part of the preoperative tests for painful TKA and when PJI is suspected. Instead, leukocyte/bone marrow scintigraphy is superior to other scintigraphic tools in diagnosis of TKA infections. Granulocyte scintigraphy, seems to be an excellent choice when the diagnosis is unclear. Moreover, nuclear diagnostic tests showed different diagnostic accuracy between TKA and THA. Conclusions: Although nuclear diagnostic tests for THA failure are superior in diagnostic accuracy compared to TKA, NM scintigraphy is still an effective tool in the identification of chronic, low grade PJI. To date, scintigraphic exams have an higher levels of sensitivity, specificity and accuracy. Currently, leukocyte/bone marrow scintigraphy is considered the gold standard for this aim. Nevertheless, further studies are needed to assess and improve the accuracy of the scintigraphic exams in order to discriminate the causes of failure for painful TKA.